Faktor-Faktor yang Berhubungan dengan Perawatan Diri Pasien Hipertensi Dewasa: Literatur Review - Sulistiawati Sulistiawati; Rika Sarfika; Esi Afriyanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Self-care in adult hypertensive patients from previous studies, it was found that only some of the variables related to self-care management were found. Comprehensive self-care has not been found from previous studies so that the limitations in accessing and studying self-care management in adult hypertensive patients are not fully comprehensive. Conduct a literature review to determine the factors of self-care management by adult hypertensive patients. A literature search was conducted through the search engine databases PubMed, ScienceDirect and Google Scholar and obtained 371 research articles and then checked the menu completeness of the research articles with a total of 238 articles. After that, a separation of criteria and a critical review stage was carried out using the Joanna Bringgs Institute (JBI) format with a total of 5 articles that were reviewed in the literature. Self-care has variables which include smoking cessation, reducing body weight if overweight, hypertension diet, regular exercise, reducing alcohol consumption, and managing stress, as well as increasing medication adherence. Factors influencing self-care include gender, age, marital status, duration of hypertension, knowledge, self-efficacy, social support and economic status. Self-care of hypertension in adulthood can be influenced by various factors, so it is suggested that future researchers can implement innovative intervention strategies needed to control related factors.